Helicobacter pylori Infection: Current Status and Future Prospects on Diagnostic, Therapeutic and Control Challenges - Ayman Elbehiry; Eman Marzouk; Musaad Aldubaib; Adil Abalkhail; Sulaiman Anagreyyah; Nuha Anajirih; Abdulaziz M. Almuzaini; Mohammed Rawway; Abdulmajeed Alfadhel; Abdelmaged Draz; Akram Abu-Okail (MDPI AG, 2023)
Helicobacter pylori (H. pylori) infection, which affects approximately half of the world's population, remains a serious public health problem. As H. pylori infection leads to a number of gastric pathologies, including inflammation, gastroduodenal ulcers, and malignancies, early detection and treatment are crucial to preventing the spread of the infection. Multiple extragastric complications, such as iron deficiency anaemia, immune thrombocytopenic purpura, vitamin B12 deficiency, diabetes mellitus, cardiovascular diseases, and certain neurological disorders, have also been linked to H. pylori infection. An awareness of H. pylori and associated health hazards is necessary to minimize or even eradicate the infection. Therefore, there is an urgent need to raise the standards for the currently employed diagnostic, eradication, alternative treatment strategies. In addition, a brief overview of traditional and cutting-edge approaches that have proven effective in identifying and managing H. pylori is needed. Based on the test and laboratory equipment available and patient clinical characteristics, the optimal diagnostic approach requires weighing several factors. The pathophysiology and pathogenic mechanisms of H. pylori should also be studied, focusing more on the infection-causing virulence factors of this bacterium. Accordingly, this review aims to demonstrate the various diagnostic, pathophysiological, therapeutic, and eradication tactics available for H. pylori, emphasizing both their advantages and disadvantages. Invasive methods (such as quick urease testing, biopsy, or culture) or noninvasive methods (such as breath tests, stool investigations, or serological tests) can be used. We also present the most recent worldwide recommendations along with scientific evidence for treating H. pylori. In addition to the current antibiotic regimens, alternative therapies may also be considered. It is imperative to eradicate the infections caused by H. pylori as soon as possible to prevent problems and the development of stomach cancer. In conclusion, significant advances have been made in identifying and treating H. pylori. To improve eradication rates, peptide mass fingerprinting can be used as a diagnostic tool, and vaccines can also eliminate the infection.